EVALUASI PENGGUNAAN LAHAN UNTUK PERKIRAAN DEBIT BANJIR RANCANGAN DI DAS CIBERANG PROVINSI BANTEN - Dessy Arianti; Kukuh Murtilaksono; Baba Barus (TATALOKA, 2015)
The Infuence of landuse change causes change of the condition of flow discharge. However, the impact of this landuse change is that the rainfall has more potential to be overland flow than infiltration. The aims of this research are: (1) to assess the patterns of rainfall of 2000, 2005, 2010 and 2014; (2) to assess the land use changes of 2000, 2005, 2010 and 2014; (3) to analyze the design discharge under land use predictions of 2028; and (4) to arrange land use planning that the peak discharge less than peak discharge of Karian Dam. Data were analysed by grid interpolation, Rational, CA-Markov. The results showed that land use of 2000–2014 change from forest to agriculture dry land area about 18.89 km2, from dry land farming to rice field area about 12.84 km2, from dry land agriculture to plantation area about 10.27 km2 and forests to plantations about 6.24 km2. The total area of land uses change of 85.39 km2 (30.2%), but the land use type which remain as existing land uses are 197.48 km2 (69.8%). Flood discharge predictions is not eligible for the best land use pattern because it exceeded the design of flood discharge of Karian Dam. The actual flood discharge is still qualify, flood discharge based on Spatial Pattern and scenarios four to synchronize the flood discharge based on Spatial Pattern is qualify for the best land use pattern. scenarios four for spatial pattern is the best land use planning to be applied that are regarded as the reference of land use in Ciberang watershed Lebak Regency of 2014-2034.